Killer whale presence in relation to naval sonar activity and prey abundance in northern Norway: - Kuningas, S.; Kvadsheim, P.H.; Lam, F.P.A.; Miller, P.J.O. (2013)
In this study, retrospective data on naval sonar activity and prey abundance were correlated with killer whale sightings within a fjord basin in northern Norway. In addition, passive acoustic and visual marine mammal surveys were conducted before, during, and after a specific navy exercise in 2006. Herring abundance was the main factor affecting killer whale presence. Naval sonar, either operational navy sonar exercises (Flotex) or experimental sonar activity (CEE) alone, did not explain killer whale occurrence. However, naval sonar activity during a period of low prey availability seemed to have had a negative effect on killer whale presence. We conclude that the level of reaction to sonar can be influenced by multiple factors, including availability of prey. © 2013 International Council for the Exploration of the Sea.